Tatar Ornament Embossed Jewelry: The Semantic Aspect - Donina, Larisa N. (Actual Problems of Theory and History of Art, 2018)
The article is based on the results of the implementation of inter-regional research project “Jewelry of Turkic peoples of Eurasia: general and special”. The handmade art of cold forging of metal products was one of the main areas of traditional ethnic culture. The significant place in Tatar jewelry is occupied by female jewelry. This study examines the regional features of technological traditions and ornamentation jewelry plaques ornamented by the method of plane embossing with notches, which was the most popular one in jewelry of Kazan Tatars from the 18th to the 19th century. They are distinguished by a common style — the flat surface relief ornament which keeps the clean smooth surface of a metal plate on the textural background. The basis of the ornamentation of metal plates served as calligraphic text handwriting “naskh” with elements of “suls” based on the Arabic alphabet. The central composition was usually decorated with a border of the same type of palmette.The paper jewelry was considered as the integral part of complex ornaments belonging to the ensemble of a traditional female costume. The features of jewelry manufacturing, the design of sign-shaped ornamentation system, the choice of motifs, and the use of technological methods allows us to deal with a number of issues of regional jewelry traditions in the context of Islamic art. The translation of texts brings us closer to the understanding of the spiritual and material heritage of Tatar people, which is part of global Muslim culture.
Keywords: calligraphy ornament; Islamic art; floral ornament; Tatar jewelry art; embossed